2011
DOI: 10.4103/0019-5154.80415
|View full text |Cite
|
Sign up to set email alerts
|

Alkaptonuria

Abstract: A case of alkaptonuria, a rare disorder with autosomal recessive inheritance, is reported here. The patient had palmar pigmentation in addition to the usual features of alkaptonuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Several studies aimed to reduce oxidative stress (for instance,, low tyrosine and phenylalanine diet, supplementation of vitamin C, or antioxidants administration) but without altering the AKU basic metabolic defect (56)(57)(58)). This predictive system will allow for the easy monitoring of oxidative stress evolution in every patient with AKU that is crucial in a chronic but not lethal disease like AKU, and it could be a good starting point in order to help clinicians in the selection of the most appropriate antioxidant treatment and in the monitoring of its efficacy by observing the trend of PTI levels (being that, actually, no credible studies have shown a significant clinical efficacy so far) (59)(60)(61). This computational method will allow for a reduction in the number of experimental studies, focusingattention on onlythe most promising treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies aimed to reduce oxidative stress (for instance,, low tyrosine and phenylalanine diet, supplementation of vitamin C, or antioxidants administration) but without altering the AKU basic metabolic defect (56)(57)(58)). This predictive system will allow for the easy monitoring of oxidative stress evolution in every patient with AKU that is crucial in a chronic but not lethal disease like AKU, and it could be a good starting point in order to help clinicians in the selection of the most appropriate antioxidant treatment and in the monitoring of its efficacy by observing the trend of PTI levels (being that, actually, no credible studies have shown a significant clinical efficacy so far) (59)(60)(61). This computational method will allow for a reduction in the number of experimental studies, focusingattention on onlythe most promising treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Though few scattered cases have been reported from India, but this seems to be a tip of the iceberg for the prevalence of this disease in India [4][5][6][7][8][9]. We report a second case of the AKU Family from Hangarki village of Dharwad District having multiple sufferers due to inheritance.…”
Section: Introductionmentioning
confidence: 91%
“…As the polymer accumulates within cartilage (Tharini et al, 2011), a process that takes many years, the normally transparent tissues become slate blue, an effect ordinarily not seen until adulthood (Verma, 2005).…”
Section: Discussionmentioning
confidence: 99%